The great outdoors: how a green exercise environment can benefit all - Gladwell, Valerie F (BioMed Central, 2013)
The studies of human and environment interactions usually consider the extremes of environment on individuals or how humans affect the environment. It is well known that physical activity improves both physiological and psychological well-being, but further evidence is required to ascertain how different environments influence and shape health. This review considers the declining levels of physical activity, particularly in the Western world, and how the environment may help motivate and facilitate physical activity. It also addresses the additional physiological and mental health benefits that appear to occur when exercise is performed in an outdoor environment. However, people’s connectedness to nature appears to be changing and this has important implications as to how humans are now interacting with nature. Barriers exist, and it is important that these are considered when discussing how to make exercise in the outdoors accessible and beneficial for all. The synergistic combination of exercise and exposure to nature and thus the ‘great outdoors’ could be used as a powerful tool to help fight the growing incidence of both physical inactivity and non-communicable disease.